Subchondral bone plate changes more rapidly than trabecular bone in osteoarthritis - Zamli, Zaitunnatakhin; Robson Brown, Kate; Sharif, Mohammed (2016)
Osteoarthritis (OA) is the most common joint disorder, characterised by focal loss of cartilage and increased subchondral bone remodelling at early OA stages of the disease. We have investigated the temporal and the spatial relationship between bone remodelling in subchondral bone plate (Sbp) and trabecular bone (Tb) in Dunkin Hartley (DH, develop OA early) and the Bristol Strain 2 (BS2, control which develop OA late) guinea pigs. Right tibias were dissected from six male animals of each strain, at 10, 16, 24 and 30 weeks of age. Micro-computed tomography was used to quantify the growth plate thickness (GpTh), subchondral bone plate thickness (SbpTh) and trabecular bone thickness (TbTh), and bone mineral density (BMD) in both Sbp and Tb. The rate of change was calculated for 10–16 weeks, 16–24 weeks and 24–30 weeks. The rate of changes in Sbp and Tb thickness at the earliest time interval (10–16 weeks) were significantly greater in DH guinea pigs than in the growth-matched control strain (BS2). The magnitude of these differences was greater in the medial side than the lateral side (DH: 22.7 and 14.75 µm/week, BS2: 5.63 and 6.67 µm/week, respectively). Similarly, changes in the BMD at the earliest time interval was greater in the DH strain than the BS2, again more pronounced in the disease prone medial compartment (DH: 0.0698 and 0.0372 g/cm3/week, BS2: 0.00457 and 0.00772 g/cm3/week, respectively). These changes observed preceded microscopic and cellular signs of disease as previously reported. The rapid early changes in SbpTh, TbTh, Sbp BMD and Tb BMD in the disease prone DH guinea pigs compared with the BS2 control strain suggest a link to early OA pathology. This is corroborated by the greater relative changes in subchondral bone in the medial compared with the lateral compartment.